2015
DOI: 10.1111/1759-5436.12173
|View full text |Cite
|
Sign up to set email alerts
|

What's Different about How Volunteers Work? Relationship Building for Wellbeing and Change

Abstract: This article looks at what happens when volunteering goes well. It provides a theoretical and empirical grounding for understanding how volunteers enable outcomes such as participation and cooperation in complex change environments. The findings point to three important qualities of volunteer relationships, which alter how people feel about themselves, others and their situation: informality, the act of doing together and networked reciprocity. When these relational styles foster three psychosocial experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Incidentally, highly balanced power relationships and equal social status are not always possible—and may not actually be desirable in some circumstances. As Aked (2015) asserted, when volunteers leverage their comparatively high social standing and comparatively influential social networks to become advocates and activists on behalf of host organizations and communities, this may actually be the most efficient route to meaningful social change. In this sense, social and economic equality are not theoretically required for effective reciprocal relationships—as long as all parties can act autonomously according to the strengths they bring to the relationship and bring these strengths to bear in equal measure (Komter, 2007).…”
Section: Modalities Of Reciprocity In International Volunteeringmentioning
confidence: 99%
“…Incidentally, highly balanced power relationships and equal social status are not always possible—and may not actually be desirable in some circumstances. As Aked (2015) asserted, when volunteers leverage their comparatively high social standing and comparatively influential social networks to become advocates and activists on behalf of host organizations and communities, this may actually be the most efficient route to meaningful social change. In this sense, social and economic equality are not theoretically required for effective reciprocal relationships—as long as all parties can act autonomously according to the strengths they bring to the relationship and bring these strengths to bear in equal measure (Komter, 2007).…”
Section: Modalities Of Reciprocity In International Volunteeringmentioning
confidence: 99%
“…However, the relational processes that link volunteering to effective social action are difficult to ascertain (Aked, , p. 32; Lough & Matthew, ). Some suggest that the personal feelings of connectedness, ability and autonomy fostered through the encounter between a volunteer and a local counterpart can galvanise social action (Aked, , p. 39).…”
Section: Relationships In International Volunteeringmentioning
confidence: 99%
“…However, the relational processes that link volunteering to effective social action are difficult to ascertain (Aked, , p. 32; Lough & Matthew, ). Some suggest that the personal feelings of connectedness, ability and autonomy fostered through the encounter between a volunteer and a local counterpart can galvanise social action (Aked, , p. 39). However, Georgeou's () detailed study of a group of Australian development volunteers identifies more complex power relationships between volunteers and local people in host organisations.…”
Section: Relationships In International Volunteeringmentioning
confidence: 99%
“…More recently, a study of the UK Voluntary Service Overseas scheme identified the relational nature of volunteer work as a distinctive feature of volunteerism, arguing that volunteering initiatives must be based on principles of mutual learning to be successful (Howard & Burns, ). One of the study's findings is that “volunteers affect positive social change through their relationships” characterised by informality (encouraging feelings of trust), networked reciprocity (fostering social commitment and a sense of ownership) and “doing together” (building new competencies by sharing responsibilities) (Aked, , p. 30). However, while volunteers may strive for reciprocity and equality in their relationships with those with whom they work, many find it difficult to “make reciprocity a feature of their relationships at the outset” due to the ways IDV programmes position them as experts able to achieve change (Aked, , p. 39).…”
Section: Relational Practices Of Idvmentioning
confidence: 99%
“…One of the study's findings is that “volunteers affect positive social change through their relationships” characterised by informality (encouraging feelings of trust), networked reciprocity (fostering social commitment and a sense of ownership) and “doing together” (building new competencies by sharing responsibilities) (Aked, , p. 30). However, while volunteers may strive for reciprocity and equality in their relationships with those with whom they work, many find it difficult to “make reciprocity a feature of their relationships at the outset” due to the ways IDV programmes position them as experts able to achieve change (Aked, , p. 39). Similarly, Georgeou's research on a long‐term Australian IDV programme discovered that volunteers “began their journey with egalitarian notions of human relations” (2012, p. 153) but found themselves placed in positions of power, status and privilege that were hard to resist or challenge.…”
Section: Relational Practices Of Idvmentioning
confidence: 99%